Extraordinary Hall Effect on Fe-Rich Amorphous Thin Films and Fe-Rich/Cu Multilayers - Michea-Mora, S; Casagrande-Denardin, J (2012)
In this study we investigated the magnetic and transport properties of thin Fe-rich amorphous films and Fe-rich/Cu multilayers. We compared the extraordinary Hall effect in these two types of samples and discussed it in terms of thickness and sample structure. The thicker films exhibited a strong in-plane magnetic anisotropy, and by decreasing film thickness both saturated Hall resistivity and Hall sensitivity increase. A Hall resistivity value of 20 ? cm is observed in 100 nm thick Fe-rich films at 12 K and a sensitivity of 1.3 /T is obtained at room temperature. Electrical conductance increases and Hall resistivity decreases when the films are sandwiched with Cu. © 2011 Elsevier B.V. All rights reserved.